(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Sylko E. M. Ecology of culture as a national oriented perspective of the cultural upbringing of the younger generation in the context of globalization. The article is dedicated to the actual problem of nature of the people protection in ecology culture. Upbringing in accordance with the nature is positioned as one of the most effective tools of humanization and greening of the socio-cultural environment, giving it a spiritual meaning.